Handbook of personology and psychopathology (John Wiley & Sons, 2005)
Personology is the study of human character in all of its complexities, covering the range of normal and pathological individuals, from evolutionary development, classification, diagnosis and measurement, to intervention at the individual, family, and societal levels. This volume, sure to become a classic in the field, provides a state-of-the-art overview of the field of personology, including personality theory, taxonomy, and assessment; diagnosis and treatment of personality disorders; and the interface between normal and abnormal personlity. The breadth and depth of this monumental work and the caliber of its contributors is unsurpassed.